Od samotności do spotkania – Wychowanie w świetle dialogiki Martina Bubera - Kiwka, Mirosław (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The aim of this paper is to present the most important elements of dialogic education, which are found in Martin Buber’s writings. Since a concept of education is usually a result of previous anthropological assumptions, the basic outlines of Buberian anthropology are presented as first. In this perspective, the education appears as an approval of the world’s view represented by the person of educator. The world proposed by Buberian educator is opened to the interpersonal community as well as opened to God and absolute values. The constitutional factor of education understood in this manner is so called “experience of the other side”, it means an act of a dialogic “embracing” of a pupil by the educator. As the main goal of the education appears to be the forming of “great characters”, it means persons spiritually consolidated and responsible, which are able to react with commitment to the uniqueness of every situation.